Translocal Childhoods and Family Mobility in East and North Europe (Studies in Childhood and Youth, 2018)
This collection explores mobile childhoods: from Latvia and Estonia to Finland; from Latvia to the United Kingdom; from Russia to Finland; and cyclical mobility by the Roma between Romania and Finland. The chapters examine how east-to-north European family mobility brings out different kinds of multilocal childhoods. The children experience unequal starting points and further twists throughout their childhood and within their family lives. Through the innovative use of ethnographic and participatory methods, the contributors demonstrate how diverse migrant children's everyday lives are, and how children themselves as well as their translocal families actively pursue better lives. The topics include naming and food practices, travel, schooling, summer holidays, economic and other inequalities, and the importance of age in understanding children's lives. Translocal Childhoods and Family Mobility in East and North Europe will be of interest to students and scholars across a range of disciplines, including sociology, anthropology and human geography.